Communicating leakage risk in the hydrogen economy: Lessons already learned from geoenergy industries - Stalker, Linda; Roberts, Jennifer J.; Mabon, Leslie; Hartley, Patrick G. (Frontiers in Energy Research, 2022)
Hydrogen is set to play a part in delivering a net zero emissions future globally. However, previous research finds that risk perception issues are particularly challenging for emerging and potentially unfamiliar technologies. Hydrogen as a fuel falls into this category. Thus, while the hydrogen value chain could offer a range of potential environmental, economic and social benefits, it is imperative that the roll-out of hydrogen fits with societal expectations of how risk ought to be managed—and by whom. Communication and engagement are critical to ensure 1) communities and stakeholders are able to come to informed decisions on hydrogen and 2) developers, operators and regulators are able to respond to societal concerns and adapt practices appropriately.Within the hydrogen value chain, geological storage may be an important step, but could present challenges in terms of perceived safety. Lessons can be learned from international research and practice of CO2 and natural gas storage in geological formations [for carbon capture and storage (CCS) and power respectively] which may be relevant to hydrogen storage in salt caverns or porous sandstones. We draw on these analogues to present potential societal risk perception issues which may arise for geological storage of hydrogen. We argue that site-specific communication and engagement strategies, underpinned by broad-based principles covering the entire span of the project and a clear rationale for how hydrogen benefits the climate and the most vulnerable members of society under an energy crisis, will be critical to fostering societal support for geological hydrogen storage.